1992
DOI: 10.1039/dt9920002161
|View full text |Cite
|
Sign up to set email alerts
|

Phosphinobenzyl- and aryl-silanes and their triosmium cluster carbonyl derivatives

Abstract: IV respectively. Reactions of the respective bidentate ligands I, II, 111 and IV with [Os,(CO),,( MeCN),] gave the novel triosmium clusters [Os,(p-H)-(CO),,(L-L)] 1,2,3 and 4 involving cleavage of one Si-H bond. Similar reactions of ligands II and IV with [Os,(p-H),(CO),,] afforded t w o new clusters [Os,(p-H),(CO),(L-L)]5 and 6 respectively. The structures of 1, 2, 4 and 5 have been determined by single-crystal X-ray diffraction techniques. In each case, the ligand assumes a chelating mode across the long edg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
2
12
0
1
Order By: Relevance
“…This cluster undergoes addition reactions with, for example, phosphines, to form clusters of formula [Os 3 H 2 (CO) 10 (PR 3 )]. It can also undergo a more complicated addition/SiH bond activation process with the functionalized phosphine HMe 2 SiC 6 H 4 CH 2 PPh 2 to afford [Os 3 H(CO) 8 (Me 2 SiC 6 H 4 CH 2 PPh 2 )] 5. In both reactions the resulting cluster core comprises a triangle in which all the OsOs bond lengths are typical of single bonds.…”
Section: Methodsmentioning
confidence: 99%
“…This cluster undergoes addition reactions with, for example, phosphines, to form clusters of formula [Os 3 H 2 (CO) 10 (PR 3 )]. It can also undergo a more complicated addition/SiH bond activation process with the functionalized phosphine HMe 2 SiC 6 H 4 CH 2 PPh 2 to afford [Os 3 H(CO) 8 (Me 2 SiC 6 H 4 CH 2 PPh 2 )] 5. In both reactions the resulting cluster core comprises a triangle in which all the OsOs bond lengths are typical of single bonds.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the reported studies of reactions of silanes with metal complexes involve tertiary silanes and examples are illustrated in Table . …”
Section: Tertiary Silanesmentioning
confidence: 99%
“…At about the same time, reactivity of the isomeric (phosphinomethyl)phenyl (Ph 2 PCH 2 C 6 H 4 −) system was investigated and found to yield ( o -((diphenylphosphino)methyl)phenyl)trimethylsilane ( o -Ph 2 PCH 2 C 6 H 4 SiMe 3 ) on quenching with chlorotrimethylsilane. Very recently, by the adoption of the reverse approach to P−C bond formation, treatment of chlorodiphenylphosphine with the (silylmethyl)phenyl Grignard reagents o -(RCH 2 )C 6 H 4 MgBr (R = SiMe 2 H, SiMeH 2 ) was examined by Ang et al For either R, however, it was found that this procedure resulted in formation of an inseparable mixture of two positional isomers, viz the ( o -phosphinobenzyl)silane (Ph 2 PC 6 H 4 CH 2 R) together with the corresponding ( o -(phosphinomethyl)phenyl)silane (Ph 2 PCH 2 C 6 H 4 R). Subsequent addition of these isomeric mixtures to triosmium dodecacarbonyl afforded altogether six novel ( o -phosphinobenzyl)silyl− and ( o −(phosphinomethyl)phenyl)silyl−triosmium carbonyl clusters {Os 3 (μ-H)(CO) 10 (μ-SiR 1 R 2 C 6 H 4 CH 2 PPh 2 ), Os 3 (μ-H)(CO) 10 (μ-SiR 1 R 2 CH 2 C 6 H 4 PPh 2 ), or Os 3 (μ-H) 3 (CO) 8 (μ-SiR 1 R 2 C 6 H 4 CH 2 PPh 2 ) for R 1 = R 2 = Me or R 1 = Me, R 2 = H}, which were separated by preparative thin-layer chromatography and then high-performance liquid chromatography.…”
Section: Introductionmentioning
confidence: 99%